Cytomegalovirus Disease in a Patient With Granulomatosis With Polyangiitis Who Also Has Splenic Necrosis - Önay GERÇİK,; Dilek SOLMAZ,; Şebnem KARASU,; Neşe EKİNCİ,; Servet AKAR, (Archives of Rheumatology, 2019)
Cytomegalovirus infection, which can occur as a result of reactivation due to immunosuppressive treatment in patients with granulomatosis with polyangiitis, is a serious condition that should be kept in mind because of its fatal course. In this article, we report a 49-year-old male patient with a diagnosis of granulomatosis with polyangiitis who developed a life-threatening colonic ulcer due to cytomegalovirus colitis and a shrunken spleen with irregular contours that was detected on abdominal computed tomography. This is a rare case of cytomegalovirus disease in a patient with granulomatosis with polyangiitis and splenic necrosis.